Postpartum feeding intervention through herbal feed supplement (Asparagus racemosus) during winter and its effect on productivity of crossbred cows - Kumar, Santosh; Mehla, R K; Dangi, R L; Lathwal, S S; Gupta, A K (The Indian Journal of Animal Sciences, 2012)
This study was undertaken to determine effect of daily minimum temperature conditions and postpartum Asparagus racemosus root powder supplementation on milk production and reproduction on freshly winter calved crossbred (Karan Fries) cows. Winter calved cows (10) with similar parity, milk production ability and body weight were subjected to experiment as ARRP (Asparagus racemosus root powder supplement @200mg/kg live body weight) and control group (n=5). Consuming similar amount of dry matter, postpartum Asparagus racemosus supplementation increased daily milk yield significantly at different daily minimum temperature during winter. With this dose level, effect of Asparagus racemosus root powder on reproduction and milk composition (fat, SNF and total solids) was not found significant. The milk yield of winter calved cows supplemented with AR was less affected to daily minimum temperature than the control un-supplemented cow (r2 = 0.38 vs. 0.54). Asparagus racemosus root powder supplement has beneficial effect on udder health of supplemented cows. Postpartum supplementation of Asparagus racemosus root powder reduced per litre cost of milk production and increased net return/day/animal. Therefore, it can be concluded that supplementation of Asparagus racemosus root powder postpartum is economically viable and beneficial to improve milk production in winter calved crossbred cows however, its potential used to ameliorate the temporary cold heat stress seems to be further studied.